(3TQM JUQja GHf GdMGLHs - (3CMeO Hf GdMSf Hf jhSa, aNQ GdOjf GdLGQHQOj , (B746 (3g` s; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdLGQHQOi deG cGf cJGH GdJUQja GdPi UfagGHf GdMGLH s
(3BNQgG (B:s
(3hgh Hdi dEeGdJgG hYdi cbhdg Ydjc s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas